Catalytic Water Oxidation by Ruthenium Complexes Containing Negatively Charged Ligand Frameworks. Issue 2 (15th March 2016) - Kärkäs, Markus D.; Åkermark, Björn
Abstract: Artificial photosynthesis represents an attractive way of converting solar energy into storable chemical energy. The H2 O oxidation half‐reaction, which is essential for producing the necessary reduction equivalents, is an energy‐demanding transformation associated with a high kinetic barrier. Herein we present a couple of efficient Ru‐based catalysts capable of mediating this four‐proton‐four‐electron oxidation. We have focused on the incorporation of negatively charged ligands, such as carboxylate, phenol, and imidazole, into the catalysts to decrease the redox potentials. This account describes our work in designing Ru catalysts based on this idea. The presence of the negatively charged ligands is crucial for stabilizing the metal centers, allowing for light‐driven H2 O oxidation. Mechanistic details associated with the designed catalysts are also presented. Abstract : Light harvesting for the production of solar fuels has been extensively investigated as an attractive approach to clean and carbon‐neutral energy. In this context, an essential component is a catalyst that is able to oxidize water to dioxygen. This account describes our group's efforts in designing Ru‐based water oxidation catalysts containing negatively charged ligand scaffolds. The benefits of incorporating these anionic ligands are presented, along with mechanistic details.